Pengembangan Aplikasi “Telesphone” untuk Pengenalan Tata Surya Menggunakan Realitas Tertambah - Addi Ammar Roofiif; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to develop a "Telesphone" application for the introduction of the Solar System using augmented reality. The development method used is the Multimedia Development Life Cycle (MDLC) which consists of six stages, namely, concept, design, material collection, manufacture, testing, and distribution. The result of this research is to produce an application for the introduction of the Solar System called "Telesphone". This application has ten Solar System planet objects that are equipped with Solar System animations, rotation features, zoom in on objects features, and information on each Solar System planetary object. Based on the results of the Black Box test, the "Telesphone" application can be used and runs well. Based on the results of testing on users, 87.5% stated strongly agree that the "Telesphone" application can help the learning process. The results of testing for the next user, 87.5% stated that they strongly agreed that the "Telesphone" application could be used as a learning medium for the Solar System